Cover Feature: Controllable Elasticity Storage and Release in CuO−Pt Core‐Shell Nanowires (ChemNanoMat 11/2018). Issue 11 (15th October 2018) - Cao, Fan; Li, Lei; Zheng, He; Wen, Guangyu; Zhao, Ligong; Liu, Huihui; Jia, Shuangfeng; Wang, Zhao; Hu, Yongming; Gu, Haoshuang; Wang, Jianbo
Abstract : One‐dimensional CuO‐Pt core‐shell heterostructures can be fabricated by depositing Pt nanoparticles onto CuO nanowires (NWs). The CuO‐Pt NWs exhibited plasticity under external compressing stress due to the permanently deformed Pt‐shell. Moreover, the deformation can be restored/released by thermal heating, suggesting the potential applications in micro/nano electro‐mechanical systems, such as mechanical energy storage and thermal sensors. More information can be found in the Full Paper by He Zheng, Jianbo Wang et al. onpage 1140 in Issue 11, 2018 (DOI:10.1002/cnma.201800368 ).